The Annual Cycle of Energy Input, Modal Excitation and Physical Plus Biogenic Turbulent Dissipation in a Temperate Lake. Issue 6 (25th June 2021) - Simpson, John H.; Woolway, R. Iestyn; Scannell, Brian; Austin, Martin J.; Powell, Ben; Maberly, Stephen C.
Abstract: A year of measurements by Doppler Current Profilers, a chain of temperature sensors and a suite of meteorological instruments has been analyzed to elucidate the seasonal cycle of the dynamical response of a temperate lake (Windermere) to surface forcing. The efficiency of energy input to the lake ( Eff ) was determined by comparing the rate of working by the surface wind‐stress RWy with the downward flux of momentum in the atmosphere. Eff was found to increase from values of ∼0.3% in winter mixed conditions, up to ∼1.2% during summer stratification, when internal seiches were present. Water column kinetic energy was similarly enhanced during stratification. Spectral analysis of the axial velocity showed that the first vertical mode was dominant during most of the stratified period with a less prominent second mode appearing in the early part of the summer. The observed periods and vertical structure of these modes generally accorded with estimates from internal wave theory based on density profiles. During stratification, pycnocline dissipation exhibited high variability linked to the surface forcing with an average, depth‐integrated, pycnocline dissipation rate of 2.5 × 10 −5  W m −2 corresponding to ∼3%–4% of RWy . Over the same period, the dissipation rate in the bottom boundary layer (BBL) exhibited a marked diurnal variation unrelated to physical forcing. Acoustic backscatter indicated the presence of vertically migrating organisms with peak aggregation in the BBL around midday coinciding with maximum dissipation. During stratification, biogenic dissipation contributed an average of ∼36% of the total BBL dissipation rate of ∼5.7 × 10 −5  W m −2 . Key Points: Increased efficiency of atmospheric energy transfer to a lake during stratification when internal seiche modes are active Dissipation measurements in the bottom boundary layer and pycnocline reveal a biogenic component by migrating organisms Determination of seiche mode activity during stratification with a test of the conformity of seiche frequencies to internal wave theory